Financial Management Behavior of The Millennial Generation in Tourism Industry at Lon Malang Beach in Sampang - Evaliati Amaniyah; Deykha Aguilika; Yustina Chrismardani (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The objective of this current research is to analyze personal financial behavior in the context of tourism in Lon Malang Beach. The current research attempts to assess to what extent personal financial behavior, financial self-efficacy, and locus of control, and the moderating influence of financial knowledge, affect individual financial behavior. The current research utilizes quantitative methodology; data is collected through field surveys and through purposive sampling on millennials who visit Lon Malang Beach. The analytical procedure is in several steps, including testing for validity, testing for reliability, and Moderate Regression Analysis (MRA). The findings of the study demonstrate that a person's financial management is positively impacted by their financial attitudes.. In addition, financial knowladge enhances financial attitudes and positively influences behavior. Furthermore, these results show that financial self-efficacy and locus of control affect how people handle their financial behavior. Building behavioral theories for individual financial management in the travel and tourist sector, particularly in Sampang, may benefit from this study.